Sensitive detection of hydroquinone using exfoliated graphene-Au/glassy carbon modified electrode. (24th January 2018) - Pogacean, Florina; Coros, Maria; Magerusan, Lidia; Rosu, Marcela-Corina; Socaci, Crina; Gergely, Stefan; van Staden, Raluca-Ioana Stefan; Moldovan, Marioara; Sarosi, Codruta; Pruneanu, Stela
Abstract: Graphene nanosheets (EGr) were electrochemically prepared through one-step exfoliation of a graphite rod in a mixture of H2 SO4 :HNO3 (3:1) at low bias (4 V). Subsequently, gold nanoparticles were attached to the graphene surface (EGr−Au) by the reduction of the metal precursor (HAuCl4 ) in aqueous solution containing dispersed graphene sheets. According to the XRD investigation, the synthesized material consists of a mixture of few-layer (86%) and multi-layer (14%) graphene. The interlayer distance was found to be in the range of 0.466–0.342 nm, which is larger than the interlayer distance in graphite (0.335 nm). The average size of gold nanoparticles in the EGr−Au sample was 24 nm, in excellent agreement with the TEM results. The synthesized material was then employed to modify a glassy carbon (GC) substrate, in order to obtain a modified electrode (GC/EGr−Au). Next, the electrochemical behavior of hydroquinone (HQ) in the presence and absence of interfering species, catechol (CAT) and bisphenol A (BPA) was studied and the corresponding calibration curves were plotted. Thus, in solutions without interfering species, the GC/EGr-Au electrode has a wide linear range (3 × 10 −7 –10 −4 M), high sensitivity (0.089 A M −1 ) and low detection limit (LOD = 10 −7 M; S/N = 3). The presence of either catechol or bisphenol A leads to the increase of LOD to 2 × 10 −7 M, and in addition changes the electrode sensitivity, up to 0.146 A M −1 .